Perlunya Representasi Gender dalam Pendidikan Agama Buddha Jenjang SMP: Analisis Konten Buku Ajar - Pranidhi, Dharmika; Wijaya Halim, Hadi (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine in depth how gender equality values are integrated into Buddhist Religious Education (PAB) at the junior high school level, based on the Merdeka Curriculum. Through a content analysis approach to character representation, women's roles, language, visual illustrations, access to Dhamma education, gender equality values, role models of female characters, students' critical reflections, and narrative-visual consistency, this study identifies significant gaps in gender representation. Using a qualitative approach, data were collected through content analysis of PAB textbooks for grades VII–IX and interviews with three Dharma teachers in Jakarta. The results show that the representation of female characters in the textbooks is very limited and the learning narratives tend to be normative without addressing structural aspects of gender inequality. The findings indicate the dominance of male characters, the lack of functional narratives about nuns and women, and the use of language and illustrations that tend to reinforce traditional gender stereotypes. Although there are attempts to mention gender equality in some chapters, the integration is not comprehensive and consistent across the materials. This article recommends the development of a more inclusive curriculum and teaching materials, encouraging balanced gender representation, and integrating gender equality values holistically in Buddhist religious education to form a more equitable and comprehensive understanding for students, as well as teacher training based on critical pedagogy and revision of learning content to reflect gender equality in Buddhist teachings.